Sleep belief factors among diploma students in UiTM Sabah / Nowyannie Willie D. Tamsin… [et al.] - Tamsin, Nowyannie Willie D.; Tuah, Norah; Sarahintu, Mazalan; Marcus, Herniza Roxanne (Universiti Teknologi MARA, Sabah, 2019)
University students are known to have different sleeping schedules. Students’ sleep difficulties will affect their health and their performances in studies. Sleep hygiene is a collection of healthy sleep habits that can improve one’s ability to fall asleep and stay asleep. It is considered to be imperative to treat sleep disturbance especially among university students. The aim of this study is to examine the sleep beliefs among the students of UiTM Sabah based on gender and academic performance. This study was conducted on Diploma students between March and July 2018. The respondents were randomly selected from Diploma students of all faculties in UiTM Sabah: Accounting, Business Management, Public Administration, Science, Planting Industry Management, Hotel Management, and Tourism Management. This paper is based on the Sleep Belief Scale questionnaire to assess the sleep hygiene awareness. Questionnaires were distributed using online survey. Findings of this study were analyzed using SPSS statistical software. The result of findings showed that the Sleep Incompatible Behaviours (drinking coffee, taking sleep medication, smoking before sleep) is the highest contributor of the students’ sleep hygiene and therefore it affects the sleep quality. While the Sleep Wake Cycle Behaviours (going to bed & waking up always at the same hour, going to bed two hours earlier than the habitual hour) and Thoughts and Attitude to Sleep (over thinking before sleep, trying to fall asleep without having a sleep sensation)also contributed to the sleep hygiene of the students but not as high as the Sleep Incompatible Behaviors. Based on the results of the findings, the counseling department of UiTM Sabah may organize an education program to create awareness among students about the intervention and prevention strategies as well as the incorrect beliefs about sleep.